Culturally-tailored plant-based interventions to improve health outcomes in pediatric populations: An integrative review - Linda Koh; Adelaide Caroci Durkin; Sarah Fiske; Uma Hingorani (Preventive Medicine Reports)
Introduction: There is an increasing rate in nutrition related health risk in children in the United States. Plant-based diets are a sustainable and cost-effective approach to prevent chronic conditions (e.g., obesity, diabetes) while lowering mortality rates. Plant-based diets should meet nutritional requirements to support appropriate growth and development. The purpose of this integrative review was to explore culturally-tailored plant-based dietary interventions to improve health outcomes in pediatric populations. Methods: A methodological review using Whittemore and Knafl's integrative approach was performed. Databases including CAB Abstracts, CINAHL, MEDLINE via PubMed, Web of Science, Food and Science Technology Abstracts, and PsycINFO were searched for peer-reviewed, primary source articles in English, between 2010 and 2025. Results: Nine articles were included. Findings focused on the specific type of cultural-tailoring used, diet types, and their role and impact on health outcomes. Discussion: Culturally-tailored plant-based interventions improved the consumption of vegetables/fruits and reduced cardiovascular risks. Support and environment were also critical in positively impacting food choices. Given health trends and the impact of plant-based diets, there is a need for more long-term studies on effective strategies to expand culturally-tailored intervention programs to improve nutrition and health outcomes among diverse and historically underrepresented pediatric populations.